Participatory modelling and development practice: artisanal fishers in Nicaragua. Issue 2 (17th February 2019) - Casillas, Christian E.; Ray, Isha
ABSTRACT: Development plans with insufficient knowledge about local realities, and that do not share technical or planning details with the target communities, bedevil development practice. This study used a form of participatory modelling in three fishing communities in Nicaragua to enable fishers to explore their economy and the potential impacts of fishery-based development projects. Co-designing a model of the fishing economy in the form of a board game created a forum in which facilitators and participants could arrive at a shared understanding of local fishing practices and the costs and benefits of strategies for addressing the fishers' priorities.